Emotional Intelligence in Islamic Religious Education Curriculum Development for Students of MI Bustanul Ulum East Lampung - Mucklis, Imam; Wati, Bertha Kusuma; Jannah, Siti Roudhotul (Kepompong Children Centre Journal, 2024)
According to Goleman, emotional intelligence is the ability to recognize one's own feelings and the feelings of others, the ability to motivate oneself and the ability to manage emotions well in oneself and in relationships with other people. The curriculum is a very determining component in an education system, therefore the curriculum is a tool to achieve an education system, therefore the curriculum is a tool to achieve educational goals and at the same time as a guideline in the implementation of teaching in an education system. all types and levels of education, the curriculum is part of the learning process which allows students to know (learning to know), learn to do something (learning to do), learn to learn, and learn to live together (learning to live Together). In this way, learning outcomes create students who are able to learn themselves, gain a certain amount of knowledge, students are able to develop it in a broader form and can apply it in everyday life.